Clinical toxicology of 'magic mushroom' ingestion. Issue 671 (September 1981) - Peden, N. R.; Macaulay, K. E. C.; Bissett, Ann F.; Crooks, J.; Pelosi, A. J.
Abstract : The clinical features are reported in 27 cases of 'magic mushroom' ingestion. Mydriasis and hyperreflexia were common as were disorders of perception and affect. Psilocybe semilanceata appears to have been the species of fungus involved.